Osteoporosis and fractures in systemic vasculitides: a systematic review and meta-analysis - Fassio, Angelo; Berti, Alvise; Mantovani, Alessandro; Adami, Giovanni; Pollastri, Francesco; Gatti, Davide; Bixio, Riccardo; Messina, Valeria; Rossini, Maurizio; Bertelle, Davide; Bertoldo, Eugenia; Galvagni, Isotta; et al. (Frontiers in Immunology, 2025)
Background/aimWe performed a systematic review and meta-analysis of observational studies aimed at investigating the prevalence of osteoporosis and osteoporotic fractures in subjects affected by systemic vasculitides (SVs) as well as to explore their risk of osteoporosis and osteoporotic fractures when compared to healthy controls.MethodsScopus, Web of Science and PubMed were systematically searched from inception to February 2024 for observational studies investigating the prevalence of osteoporosis and fragility fractures in adults with SVs. In addition, when available, we assessed the odd ratios (OR) of prevalent osteoporosis and fragility fractures amongst subjects with SVs vs. healthy controls. Data from eligible studies were extracted, and meta-analysis was performed using a random effects model to obtain ORs with 95% confidence intervals (CIs). Subgroup analyses and meta-regressions were also performed. This study was registered in Open Science Framework (DOI: https://doi.org/10.17605/OSF.IO/3G7RJ).ResultsForty studies with 23,358 individuals affected by SVs were included. The overall prevalence of osteoporosis and fragility fractures in the SV patients were respectively 14.64% (95%CI 12.21-18.89), and 17.08% (95%CI 11.42-24.78). The ORs for osteoporosis and fragility fractures in SV patients when compared with healthy controls were 2.92 (95%CI 1.72-4.98) and 2.39 (95%CI 1.34-4.26) respectively. The univariable meta-regression analysis showed a significant association between cumulative glucocorticoids’ dosage (total grams) and risk of prevalent osteoporosis (estimate = 0.0995, R2 = 0.24, p=0.0194).ConclusionSVs are associated with an increased risk for osteoporosis and fragility fractures, suggesting that active vigilance and pre-emptive screening are recommended.Systematic review registrationhttps://archive.org/details/osf-registrations-3g7rj-v1.